Diseño de un artbook, mediante la antropomorfización de las principales deidades de la cosmovisión shuar - Suntaxi Socasi, Jonathan Paúl (2017)
This research work consists of the anthropomorphic representation of the main mythological deities of the Shuar worldview, through the creation of an artbook makes up by vector illustrations; with a personal overview which look for generating knowledge about illustration process of each character to set up a graphic style as reference in creation of new graphic projects. in addition, establishing the artbook as a way of cultural information and for the preservation of the heritage, memory of Shuar culture and mythology. The lack of graphic evidence, social awareness and problems for accessing to information of Shuar mythology led to the development of the present project. The methodology used to carry out the research project is the documentary research, which allowed the inquiry and interpretation of information expressed in previous researches.